Strategi Pemasaran DOC Ayam Ras Pedaging pada CV Missouri, Bandung Jawa Barat - Jamarizal, -; Suryahadi, -; Syarief, Rizal (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2017)
Broiler farming business is inseparable from several obstacles encountered. The obstacles are the high risk faced by broiler breeding business such as the risk of price fluctuation, both input prices such as DOC, feedmill and medicines as well as selling price of livebird and carcass fluctuation. Another risk faced by broiler farming is the production risk caused by weather, climate, diseases and social risks. The purpose of this research was (1) to describe factors faced by CV Missouri in marketing broiler DOC, (2) to describe the strategy run by CV Missouri in coping with factors in the marketing of broiler DOC, and (3) to determine the alternative form of marketing strategy developed by CV Missouri in marketing broiler DOC. CV Missouri’s strategic position based on IE matrix is in quadrant V. It means that the company has a good growth strategy and stability. Moreover, marketing strategies of DOC in CV Missouri based on SWOT analysis are (a) expanding network marketing optimally; b) creating a better DOC by increasing productivity; and (c) increasing the company's capital to compete with competitors, therefore additional capital is required to make market opportunities wider. Alternative strategies which could be implemented by CV Missouri based on QSP matrix analisys are (1) keeping and maintaining the quality of products produced, (2) improving services and consumers loyalties.